THE IMPORTANCE OF AUTOMATION IN THE AUTOMOTIVE INDUSTRY WELDING SYSTEM - Pinto, Aline Cristina Lamas; Okada, Roberto Hirochi (Revista Interface Tecnológica, 2022)
The resistance spot welding process is widespread in industry. automotive industry, currently the most applied in the union of the various types of plates that form the bodywork. In relation to welding processes by opening an electric arc, it has the main advantages of providing less heating to the joined parts, since the fusion is restricted only to the place where the point forms, not adding extra weight to the product, since it does not uses addition materials in addition to providing lower costs. Currently, the welding machine guarantees a lot of efficiency and productivity in the process of joining metals, avoiding common mistakes and the unnecessary disposal of raw material, which is why they have been one of the most used. It is very important to know the methods so that you can identify when to use each one. It is important to point out that in order to carry out the welding process, in any situation, it must be carried out by a qualified professional, and use the necessary PPE so that it happens in a safe and reliable way, avoiding possible accidents. The central objective is to verify the studies through a survey of data, critical and favorable factors on the chosen theme. We can therefore conclude that the welding process is an industry branch in which it will bring greater demands, challenges and requirements over time, mainly due to the constant growth of gas and oil exploration, also reflected by the increase in energy consumption.